Perceptions and experiences of Finnish upper-secondary school students regarding guidance and counselling services - Kavlak, Yasar (2018)
The primary aim of this research is to comprehend the perceptions and experiences of Finnish general upper-secondary school students towards the guidance and counseling services. The study utilized the evaluation of educational outcomes model and efficacy of guidance and counseling services design to analyze the students’ perspectives on the guidance and counseling services. The data was gathered from two urban schools which are located in the central region of Finland, and there were 238 participants. The results showed that the students rated the provided guidance and counseling services between moderate and poor. Furthermore, the research found that there was a statistically significant difference between gender in the perceptions of students. Also, the outcomes of the study proved that there was a statistically significant difference between the grade levels in the perceptions of the students regarding the guidance and counseling services. Lastly, the research results showed that there was a correlation between the goals of the students and the perceptions of the students regarding the guidance and counseling services.